Clinical Implications of Pan-Immune-inflammatory Values in Patients with Hypertrophic Cardiomyopathy - Levent PAY; Ahmet Cagdas YUMURTAS; Seyda DERELI; Tugba CETIN; Hikmet KADI; Tufan CINAR; Mert Ilker HAYIROGLU (Medeniyet Medical Journal)
Objective: Despite significant advances in understanding hypertrophic cardiomyopathy (HCM) in recent years, there is a need to improve risk stratification for patients at high risk of adverse outcomes. The relationship between inflammation and disease severity in HCM patients is known. Recently, a new inflammation parameter called the pan-immune inflammation value (PIV) has been introduced. However, the relationship between PIV and HCM has not yet been examined. Hence, we aim to investigate the effect of PIV on prognosis in a large series of HCM patients. Methods: The study included 389 consecutive patients with HCM admitted to a tertiary care hospital between 2004 to 2021. The PIV for patients was calculated as: Neutrophil count x platelet count x monocyte count / lymphocyte count. The cohort was categorized into three groups according to PIV, and the association between these groups and long-term mortality was evaluated. Results: Over an average follow-up period of 55.5+-12.7 months, long-term mortality occurred in 47 out of 389 patients. Long-term mortality was recorded in 7 patients in tertile 1, 12 patients in tertile 2, and 28 patients in tertile 3. Multivariate regression analysis revealed that long-term all-cause mortality was 3.5 times higher in tertile 3 compared to tertile 1. The receiver-operating characteristic curve based on the PIV had 62% sensitivity and 65% specificity for long-term mortality. Conclusions: High PIV levels may serve as a predictor of long-term mortality in patients with HCM. PIV could be a useful screening tool for identifying HCM patients at increased risk of adverse outcomes.